Socio-philosophical foundations of the mythology of transhumanism - Mazeikiene, N.; Starovik, P. (KSU Publ., 2020)
The article identifies the challenges that humanity poses to the current situation of global cultural disorientation, shifting emphasis from universal values to the standards of mass culture. An attempt was made to systematically expound the reasons and key points in the transition of thinking and subsequent actions that made it possible to create conditions for abandoning historically established worldviews for the sake of ideological clichés and creating a new practice — deifying the technical justification of the surrounding subject of space and creating their own ontology from ready-made blocks of destroyed structures. The main problem has been posed that the new ontology makes the subject as autonomous from the burden of traditional «conventions» as possible and ultimately causes extreme distrust of the constructions of the «other», «others».
Трансгуманизм мифологиясының əлеуметтік-философиялық негіздері
Социально-философские основания мифологии трансгуманизма
Keywords: man; subject; individual; transhumanism; metaphysics; reason; reason; tradition